Implementation Of Legislation Functions In The Process Of Making Regional Regulations Initiative Of Regional People's Representative Council Of Singkawang City - Usmulyadi, Syarif; Elyta, Elyta; Qadrie, Syarif Redha Fachmi Al (PT. Riset Press International, 2024)
Implementation of the legislative function in the process of making Regional Regulations initiated of Singkawang City is a process that involves critical steps to create regulations that are relevant and effective for the interests of the local community. The Singkawang City Regional People's Representative Council, as a legislative institution, has a central role in drafting and ratifying regional regulations, which summarize the aspirations and needs of the community. This process begins with identifying problems or conditions that need to be regulated, continues with drafting regional regulations, and involves various stages of public consultation to obtain input from multiple parties. Apart from that, the Singkawang City Regional People's Representative Council is also tasked with evaluating and ensuring the conformity of the draft Regional Regulation with applicable Legislation. Decision to ratify the Regional Regulation reflects joint efforts in formulating policies that accommodate the community's interests. Therefore, transparency, accountability, and public participation are vital in ensuring that every regional regulation produced reflects the real needs of the people of Singkawang City and is by applicable legal norms. Thus, implementing the legislative function by the Singkawang City Regional People's Representative Council is an essential foundation for building a fair and just legal order to improve the welfare of the local community.